Infraestrutura e concorrência: o caso dos aeroportos brasileiros - Renzetti, Bruno Polonio (2018)
There are many challenges in projects for the concession of infrastructure. Such challenges are even greater when it comes to insert private players in an economic sector previously monopolized by a state-owned company. This thesis seeks to provide a consistent picture of the concessions of Brazilian airports started in 2011, focusing especially on the potential anticompetitive effects of clauses inserted in the bidding terms. It also investigates how the Brazilian airport sector has evolved in the last years and the motives that made the Federal Government initiate the privatization of its largest airports. The study focus mainly on the rules for participation and qualification requirements for the bidders. We understand that many of the rules of the bidding terms have anticompetitive effects. The study here conducted is able to shed light on the evolution of the terms since the first round of concessions, in 2011, until the last, in 2017. It is mandatory that the Administration revisit and rethink the terms every new round of concessions, assessing if they were able or not to achieve the projected goals for the project. The present thesis argues that the way in which the airports concession was projected was not able to foster competition, even though some relevant changes were seen since the first round of concessions. Suggestions in order to enhance and improve competition in the next round of concessions are made at the end.